Investment Promotion; Foreign Direct Investment Determinants and Policy Framework Analysis for India: Lessons for Zimbabwe - Muchinguri, Tawanda (Graduate School of Business (GSB), 2018)
Today Zimbabwe finds itself on the cusp of a new era, an inflection point which should set the country on a path towards recovery and sustainable economic growth, after years of being in a socio-economic quagmire yet extravagantly endowed with natural resources and extraordinary human capital. This study seeks to examine how best to unlock this untapped and embedded value for the emancipation of Zimbabwe’s people by looking at how other countries have extricated themselves from similar situations by the use of foreign direct investment. Pursuant to this cause, the author identified India as a case study from which Zimbabwe can learn and thus seeks to identify and measure the determinants of foreign direct investment and understand the policy framework underlying these determinants. Gross domestic product, trade, the exchange rate, inflation, foreign reserves and the foreign direct investment restrictiveness index were employed as variables in the research using annual data over a 27 year period from 1990 to 2016. This period was deliberately chosen to capture the impact of the liberalisation and reform efforts which set India on a growth path and today is the biggest recipient of greenfield foreign direct investment. The autoregressive distributed lag cointegration framework was employed as an estimation technique to examine the long-run relationship between foreign direct investment and the chosen explanatory variables. The findings reveal that the exchange rate and the foreign direct investment restrictiveness index are the key determinants of FDI in India with a negative relationship, thus a stronger Indian rupee and better restrictiveness index rating lead to more foreign direct investment inflows. Based on the results, placed in the context of India’s foreign direct investment policy framework, the study makes bespoke and befitting recommendations to the Zimbabwean authorities on how to use the import and the tenets of the foreign direct investment restrictiveness index as a basis for devising far reaching reforms needed to attract foreign direct investment for the sustainable development of Zimbabwe.